2005
DOI: 10.1007/s00246-005-0969-5
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of Atrial Septal Defect in the Pediatric Population

Abstract: Our recent experience indicates that patients with a hemodynamically significant atrial septal defect secundum (ASD2) do not necessarily present with classic physical and electrocardiographic (ECG) findings. The purpose of the study was to review the records of patients either receiving a catheter device or undergoing surgical repair for the closure of ASD2 to determine their initial physical and ECG findings. Therefore, we did a retrospective review of 47 consecutive patients who had echocardiographic evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 6 publications
1
10
1
Order By: Relevance
“…Most ASDs were traditionally diagnosed based on symptoms such as heart murmur, cardiomegaly and chest pain [2]; however, in modern practice, echocardiography is frequently used as a tool in neonatal units to evaluate respiratory problems or cardiomegaly and to examine benign murmurs in otherwise healthy babies. Notably, however, this use of echocardiography has also led to the incidental discovery of ASDs.…”
Section: Introductionmentioning
confidence: 99%
“…Most ASDs were traditionally diagnosed based on symptoms such as heart murmur, cardiomegaly and chest pain [2]; however, in modern practice, echocardiography is frequently used as a tool in neonatal units to evaluate respiratory problems or cardiomegaly and to examine benign murmurs in otherwise healthy babies. Notably, however, this use of echocardiography has also led to the incidental discovery of ASDs.…”
Section: Introductionmentioning
confidence: 99%
“…Christensen et al evaluated 47 patients whose median defect diameter was 13 mm and detected normal ECG findings in only 18% of cases. [10] Azhari et al detected right ventricular conduction delay in 88% of 121 patients, and demonstrated increases in right ventricular and atrial load on ECG in parallel with increase in defect diameter. [11] Outcomes of present study were similar to those in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…[14] They reported similar median age of patients to our study (at last follow-up), however, used different ASD size ranges. The remaining studies included either smaller patient cohorts of 20–47 patients with an older mean age of 7.7 years[121317] and/or included a select patient population referred for ASD closure. [131417] In the study by Schiller et al ., the reported RSR’ prevalence combined RSr’, rSR’, and QR patterns in lead V1.…”
Section: Discussionmentioning
confidence: 99%
“…[121314151617] This pattern is rarely described in normal patients as well. This rSR’ pattern is hypothesized to correlate with RV enlargement rather than a conduction disturbance.…”
Section: Introductionmentioning
confidence: 99%